2012
DOI: 10.1371/journal.pone.0050184
|View full text |Cite
|
Sign up to set email alerts
|

Spectro-Temporal Weighting of Loudness

Abstract: Real-world sounds like speech or traffic noise typically exhibit spectro-temporal variability because the energy in different spectral regions evolves differently as a sound unfolds in time. However, it is currently not well understood how the energy in different spectral and temporal portions contributes to loudness. This study investigated how listeners weight different temporal and spectral components of a sound when judging its overall loudness. Spectral weights were measured for the combination of three l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 76 publications
8
29
2
Order By: Relevance
“…These calculate the contribution of individual harmonics using the critical band rate scale, so that lower harmonics fall in different critical bands, but higher harmonics may fall into the same critical band. This means that higher frequency components in the spectrum contribute less to loudness, as is also seen in the data of Oberfeld et al (2012). So, as the spectral centroid shifts toward higher frequencies, there will be a point at which the slope of loudness increase will flatten, as observed in the present data.…”
Section: Loudnesssupporting
confidence: 81%
“…These calculate the contribution of individual harmonics using the critical band rate scale, so that lower harmonics fall in different critical bands, but higher harmonics may fall into the same critical band. This means that higher frequency components in the spectrum contribute less to loudness, as is also seen in the data of Oberfeld et al (2012). So, as the spectral centroid shifts toward higher frequencies, there will be a point at which the slope of loudness increase will flatten, as observed in the present data.…”
Section: Loudnesssupporting
confidence: 81%
“…The increased weight assigned to low frequencies might then be attributed to the presence of steeper loudness functions at low frequencies. Oberfeld et al (2012) considered this explanation for the low-frequency effect observed in their data and found that the predicted effect on perceptual weights was smaller than the observed effect. For the present conditions, any effect of steeper loudness functions at low frequencies should have been observed in the predictions generated by the model because it assumes steeper loudness functions at low frequencies, although the difference at 250 Hz is small.…”
Section: Observed Data Vs Predictions Of the Loudness Modelmentioning
confidence: 99%
“…Most of the previous uses of sample discrimination have given listeners correct-answer feedback (e.g., Doherty and Lutfi, 1996;Lutfi and Jesteadt, 2006;Oberfeld et al, 2012), and all but Oberfeld et al described it to listeners as an intensity resolution task rather than one involving judgments of overall loudness. Results reported here may have been different if the listeners had been given a more complete description of the properties of the stimuli and feedback regarding their answers, but the intent was to make the loudness and sample-discrimination tasks comparable, not to emphasize potential differences.…”
Section: Loudness Judgments Vs Sample Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, temporal weights of loudness have been assessed mainly for sounds with flat intensity profiles (e.g., Pedersen and Ellermeier, 2008;Oberfeld and Plank, 2011;Oberfeld et al, 2012). Using experimental designs based on molecular a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%